PENGARUH ORGANIZATIONAL CULTURE TERHADAP EMPLOYEE PERFORMANCE PADA PT POS INDONESIA - Meilia Risna (MANAJEMEN, 2023)
This study aims to analyze the influence of organizational culture on employee performance at PT Pos Indonesia. Organizational culture plays an important role in creating a conducive work environment, increasing employee loyalty, and encouraging more productive work behavior. The research method used is a quantitative approach with data analysis techniques using the Structural Equation Modeling (SEM) model based on SmartPLS. The research sample consisted of 350 respondents who were employees of PT Pos Indonesia. The results of the study indicate that organizational culture has a positive and significant influence on employee performance. The stronger the organizational culture that is applied, the higher the level of employee satisfaction and motivation in working. In addition, this study found that Organizational Citizenship Behavior (OCB) acts as a mediating variable in the relationship between organizational culture and employee performance. Employees who have a high awareness of organizational values ​​tend to show better work behavior, thus having a positive impact on achieving company goals. As a practical implication, PT Pos Indonesia needs to strengthen the internalization of organizational culture through ongoing training and socialization. In addition, a fair reward system and effective organizational communication must be improved so that employees feel appreciated and more motivated to contribute to achieving the company's vision. Keywords: Organizational culture, employee performance, Organizational Citizenship Behavior.